A National Survey of Transplant Surgeons and Nephrologists on Implementing Apolipoprotein L1 (APOL1) Genetic Testing Into Clinical Practice. (March 2019) - Gordon, Elisa J.; Wicklund, Catherine; Lee, Jungwha; Sharp, Richard R.; Friedewald, John
Introduction: There is debate over whether Apolipoprotein L1 (APOL1) gene risk variants contribute to African American (AA) live donors' (LD) increased risk of kidney failure. Little is known about factors influencing physicians' integration of APOL1 genetic testing of AA LDs into donor evaluation. Design: We conducted a cross-sectional survey, informed by Roger's Diffusion of Innovations theory, among nephrology and surgeon members of the American Society of Nephrology, American Society of Transplantation, and American Society of Transplant Surgeons about their practices of and attitudes about APOL1 genetic testing of AA potential LDs. Descriptive statistics and bivariate analyses were performed. Results: Of 383 completed surveys, most physicians believed that APOL1 testing can help AA LDs make more informed donation decisions (87%), and the addition of APOL1 testing offers better clinical information about AA LD's eligibility for donation than existing evaluation approaches (74%). Among respondents who evaluate LDs (n = 345), 63% would definitely or probably begin or continue using APOL1 testing in the next year, however, few use APOL1 testing routinely (4%) or on a case-by-case basis (14%). Most did not know the right clinical scenario to order APOL1 testing (59%), but would use educational materials to counsel AA LDs about APOL1 testing (97%). Discussion: Although physicians were highly supportive of APOL1 genetic testing for AA LDs, few physicians use APOL1 testing. As more physicians intend to use APOL1 testing, an ethical framework and clinical decision support are needed presently to assist clinicians in clarifying the proper indication of APOL1 genetic testing.